EVALUATION OF EPIZOOTIC SITUATION WITH MAREK’S DISEASE VIRUS IN UKRAINE - Д. С. Бережна; О. А. Іващенко; В. П. Поліщук (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2015)
Aim. To evaluate epizootic situation of Marek’s disease virus in Ukraine. Methods. Poultry with characteristic clinical features to Marek’s disease virus were investigated by histopathological analysis to prove the research we have used nested-PCR. Results. As a result of studies it was found a virus in poultry farms of Kyiv, Cherkasy, Khmelnytsky, Poltava, Dnipropetrovsk, Kirovograd, Zaporizhye, Mykolaiv, Donetsk, Vinnytsia, Volyn, Ivano-Frankivsk, Zhytomyr, Rivne, Transcarpathian regions of Ukraine and Crimea. There were shown increasing the number of infected poultry in 2012 and 2013 and changes in the degree of infestation of poultry by Marek’s disease virus. Conclusions. As a result of three years of study we have found that Marek’s disease virus has been circulating in 14 regions of Ukraine and Crimea. Taking into consideration the increasing prevalence and active trade relations between Ukraine poultry farms, it is necessary to implement a more rigid system of control over MDV.